Implementation and Operational Research: Distance From Household to Clinic and Its Association With the Uptake of Prevention of Mother-to-Child HIV Transmission Regimens in Rural Zambia. (1st November 2015) - Escamilla, Veronica; Chibwesha, Carla J.; Gartland, Matthew; Chintu, Namwinga; Mubiana-Mbewe, Mwangelwa; Musokotwane, Kebby; Musonda, Patrick; Miller, William C.; Stringer, Jeffrey S. A.; Chi, Benjamin H.
Abstract : Background: In rural settings, HIV-infected pregnant women often live significant distances from facilities that provide prevention of mother-to-child transmission (PMTCT) services. Methods: We offered universal maternal combination antiretroviral regimens in 4 pilot sites in rural Zambia. To evaluate the impact of services, we conducted a household survey in communities surrounding each facility. We collected information about HIV status and antenatal service utilization from women who delivered in the past 2 years. Using household Global Positioning System coordinates collected in the survey, we measured Euclidean (i.e., straight line) distance between individual households and clinics. Multivariable logistic regression and predicted probabilities were used to determine associations between distance and uptake of PMTCT regimens. Results: From March to December 2011, 390 HIV-infected mothers were surveyed across four communities. Of these, 254 (65%) had household geographical coordinates documented. One hundred sixty-eight women reported use of a PMTCT regimen during pregnancy including 102 who initiated a combination antiretroviral regimen. The probability of PMTCT regimen initiation was the highest within 1.9 km of the facility and gradually declined. Overall, 103 of 145 (71%) who lived within 1.9 km of the facility initiated PMTCT versus 65 of 109 (60%) who lived farther away. For every kilometer increase, the association with PMTCT regimen uptake (adjusted odds ratio: 0.90, 95% confidence interval: 0.82 to 0.99) and combination antiretroviral regimen uptake (adjusted odds ratio: 0.88, 95% confidence interval: 0.80 to 0.97) decreased. Conclusions: In this rural African setting, uptake of PMTCT regimens was influenced by distance to health facility. Program models that further decentralize care into remote communities are urgently needed. Abstract : Supplemental Digital Content is Available in the Text.